Osteoblastic Metastases Mimickers on Contrast Enhanced CT - Fahad Al-Lhedan; Sam Samaan; Wanzhen Zeng (Case Reports in Radiology)
Secondary osseous involvement in lymphoma is more common compared to primary bone lymphoma. The finding of osseous lesion can be incidentally discovered during the course of the disease. However, osseous metastases are infrequently silent. Detection of osseous metastases is crucial for accurate staging and optimal treatment planning of lymphoma. The aim of imaging is to identify the presence and extent of osseous disease and to assess for possible complications such as pathological fracture of the load-bearing bones and cord compression if the lesion is spinal. We are presenting two patients with treated lymphoma who were in complete remission. On routine follow-up contrast enhanced CT, there were new osteoblastic lesions in the spine worrisome for metastases. Additional studies were performed for further evaluation of both of them which did not demonstrate any corresponding suspicious osseous lesion. The patients have a prior history of chronic venous occlusive thrombosis that resulted in collaterals formation. Contrast enhancement of the vertebral body marrow secondary to collaterals formation and venous flow through the vertebral venous plexus can mimic the appearance of spinal osteoblastic metastases.